FLEXURE OF LITHOSPHERE AND CONTINENTAL-MARGIN BASINS - Watts, A; Ryan, W (1976)
The accumulation of sediments at an Atlantic-type continental margin constitutes a load on the lithosphere which simply sags due to its weight. Studies of the geometry of deformation suggests the lithosphere will respond to these loads either by local loading of an Airy-type crust or flexural loading of a strong rigid crust. The authors used biostratigraphic data from commercial boreholes from the Gulf of Lion and the East Coast, U. S. A. to quantitatively determine the contribution of sediment loading to the subsidence. From these data they determined sea-floor and basement depths for sequential time intervals during margin development. The nature of the subsidence is discussed and comparisons are made with that which would be expected from thermal-contraction models.